Analysis of Human Resources Management in Improving Learning Strategies at MAN 2 Situbondo During the Covid-19 Pandemic - Turmudi, Imam (Didaktika Religia, 2022)
This  study aimed to  determine  learning  strategies  in  the New Normal Era. In the last few years, Indonesia especially experienced the Covid 19 disaster, which caused all elements of life to experience a new era to live life. This field study was conducted at the Madrasah Aliyah Negeri 2 Situbondo institution because the institution in the teaching and learning process must use effective and efficient strategies to support ongoing learning and to find out Analysis  of  Human  Resource  Management  in  the  New  Normal  Era’s  improving  learning  strategies. The method employed  in  this  study  is  a  qualitative  descriptive  analysis study strategy. In the new normal era, human resource management enhances learning techniques through efforts, mature readiness, and debriefing in terms of Information Technology abilities and virtual learning habits, according to the survey results. The most effective learning method in the new normal period is to adhere to the regulations set forth by the Ministry of Education and Culture regarding  virtual  learning  on a platform that has been approved. In  order  to  reduce  misunderstandings  between  teachers  and  students,  it is essential that both students and teachers have the necessary tools, credentials, and awareness of the factors that will determine the course of learning. To prevent lying, being lazy, and cheating on tests, students study at home under the guidance and supervision of their parents. in order to maintain the standards of ethics, morals, and norms in academia.